The Effectiveness of the Problem-Based Learning Model on the Critical Thinking Skills of Buddhist Education Students - Setiawan, Panya Dama; Partono, Partono; Utami, Sri (Lembaga Sosial Rumah Indonesia, 2025)
Purpose – This study examines the impact of Problem-Based Learning (PBL) on students' critical thinking skills in Buddhist religious education at SMA Bhakti Karya Kaloran, addressing the significance of critical thinking as a core 21st-century competency and the scarcity of research applying PBL in spiritually and contemplatively oriented religious contexts like Buddhism.Method – This study employed a quantitative approach with a correlational design. The research sample consisted of 25 Buddhist students, selected using a saturated sampling technique. Data was collected through a Likert-scale questionnaire that had been tested for validity and reliability and were analyzed using simple linear regression with the assistance of SPSS version 21. Findings – The research findings indicate that the Problem-Based Learning (PBL) model has a significant influence on students' critical thinking skills, with a coefficient of determination (R²) of 0,535. This suggests that 53,5% of the variation in critical thinking ability can be explained by the implementation of the PBL model. The most prominent aspects of the PBL model were social engagement and psychomotor involvement, while the highest dimension of critical thinking was in the interpretative aspect. The significance value (0.000 < 0.05) and the t-value (5.141 > t-table) confirm a significant relationship between the two variables. Research Implications – This study makes an important contribution to enriching the literature on Buddhist education through a participatory and contextual learning approach. However, its limitations lie in the small sample size and the restricted scope to a single school, which prevents the results from being widely generalized. Further research is recommended to employ a larger sample and a more robust experimental design to explore causal relationships and other mediating factors such as learning motivation and the internalization of religious values.